ON JUSTIFICATION OF STANDARDS FOR NATURAL RADIONUCLIDE CONCENTRATION IN FACING PRODUCTS AND MATERIALS - I. P. Stamat; D. I. Stamat (Радиационная гигиена)
The article addresses issues of the population radiation protection regulatory framework development for the natural sources of radiation. Calculations for justification of standard for natural radionuclide concentration in the wide range of contemporary building materials - facing products - are formulated. The basic consideration of calculations is that implementation of these products could lead to the additional population exposure from natural sources less than 0,1 mSv/year. On the base of this assumption it is shown that effective specific activity of natural radionuclides in these products must not exceed 740 Bq/kg.